Implementation strategies of a crm system from an endomarketing perspective to foster positive organizational behavior - López Salazar , José Luis; López Aguirre, José Fernando; Pomaquero Yuquilema, Juan Carlos; Vasco Vasco, Jorge Antonio (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2023)
A company with a strategic vision oriented towards business relationships seeks to adopt tools that help it achieve this goal. One of these tools could be Customer Relationship Management (CRM), which places the employee at the center of the organization, thus improving employee satisfaction and engagement. This, in turn, leads to optimized profitability and increased productivity in any type of business. Despite the existence of previous research on this topic, it is still necessary to deepen the analysis of the implications of the implementation of CRM tools.